The Combination of Chest Computed Tomography and Standard Electrocardiogram Provides Prognostic Information and Pathophysiological Insights in COVID-19 Pneumonia - Bertini, Matteo (J Clin Med, 2021)
Aims. Several studies have unveiled the great heterogeneity of COVID-19 pneumonia. Identification of the “vascular phenotype” (involving both pulmonary parenchyma and its circulation) has prognostic significance. Our aim was to explore the combined role of chest computed tomography (CT) scan and electrocardiogram (ECG) at hospital admission in predicting short-term prognosis and to draw pathophysiological insights. Methods and Results. We analyzed the chest CT scan and ECG performed at admission in 151 consecutive COVID-19 patients admitted between 20 March and 4 April 2020. All-cause mortality within 30 days was the primary endpoint. Median age was 71 years (IQR: 62–76). Severe pneumonia was present in 25 (17%) patients, and 121 (80%) had abnormal ECG. During a median follow-up of 7 days (IQR: 4–13), 54 (36%) patients died. Deceased patients had more severe pneumonia than survivors did (80% vs. 64%, p = 0.044). ECG in deceased patients showed more frequently atrial fibrillation/flutter (17% vs. 6%, p = 0.039) and acute right ventricular (RV) strain (35% vs. 10%, p < 0.001), suggesting the “vascular phenotype”. ECG signs of acute RV strain (HR 2.46, 95% CIs 1.36–4.45, p = 0.0028) were independently associated with all-cause mortality in multivariable analysis, and in the likelihood ratio test, showed incremental prognostic value over chest CT scan, age, and C-reactive protein. Conclusions. Combining chest CT scan and ECG data improves risk stratification in COVID-19 pneumonia by identifying a distinctive phenotype with both parenchymal and vascular damage of the lung. Patients with severe pneumonia at chest CT scan plus ECG signs of acute RV strain have an extremely poor short-term prognosis.